Multi-disciplinary team approach in the management of connective tissue disease-interstitial lung disease: The way forward - Ben Rowlands; Puja Mehta; Harsha Gunawardena (Indian Journal of Rheumatology)
Interstitial lung disease (ILD) is a heterogeneous group of diffuse parenchymal lung disorders and is a common manifestation of autoimmune connective tissue disease (CTD). In some patients, ILD is associated with a clinical spectrum, whereas in some cases it is the presenting or dominant feature. A prompt and correct diagnosis of CTD-ILD is paramount, as early recognition and intervention are essential to deliver an optimal patient pathway and clinical outcomes. This requires detailed clinical assessment of pulmonary and extra-pulmonary disease, robust autoimmune serological testing, review of radiological patterns, and appropriate treatment pathways. We describe the key components required for multidisciplinary evaluation of patients with CTD-ILD, highlighting the need for collaborative working between specialist teams to provide high-quality care.